Botanical origin and geographic differentiation of bee-pollen produced in high mountains from the Colombian eastern Andes. Issue 5 (3rd September 2017) - Chamorro, Fermín J.; León, Daniela; Montoya-Pfeiffer, Paula M.; Solarte, Víctor M.; Nates-Parra, Guiomar
Abstract: In the high mountains of the Colombian Eastern Cordillera (~2000–3000 m above sea level), at the Altiplano Cundiboyacense region and surroundings, beekeepers have specialised in pollen production with substantial harvests all year round. Despite this productive advantage, the knowledge about plants used by honeybees as pollen resources is still limited. Hence, the aim of this work was to identify the botanical origin of bee pollen from this region and to examine differences between five distinguished sub-regions: Sabana de Bogotá, Fúquene, Márquez, Tundama and Norte-Gutiérrez. By means of palynological analyses of 86 pollen samples produced between 2008 and 2010, we found a total amount of 126 pollen types, most of them belonging to the families Asteraceae and Fabaceae. Major pollen types correspond to the exotic taxa Hypochaeris radicata, Brassicaceae, Eucalyptus globulus, Trifolium repens, Trifolium pratense and the native taxa Quercus humboldtii and Weinmannia sp. Differences between sample groups from the five sub-regions were mainly associated to variations in pollen abundance and frequency of native plant species. This result highlights the potential for commercialising bee-pollen from the Colombian Eastern Cordillera with geographical origin differentiation, as well as the importance for beekeeping in promoting the conservation of the natural ecosystems from the region.